The association between chronic deciduitis and preeclampsia. (March 2022) - Morimune, Aina; Kimura, Fuminori; Moritani, Suzuko; Tsuji, Shunichiro; Katusra, Daisuke; Hoshiyama, Takako; Nakamura, Akiko; Kitazawa, Jun; Hanada, Tetsuro; Amano, Tsukuru; Kushima, Ryoji; Murakami, Takashi
Highlights: Preeclampsia is frequently found in pregnants with chronic deciduitis. Chronic deciduitis is frequently found in pregnants with preeclamsia. Chronic deciduitis is related to poor perinatal outcomes. Abstract: Chronic deciduitis (CD) is slight inflammation of the decidua found during pregnancy. The cause of preeclampsia is thought to be placental hypoplasia, and various theories have been proposed to explain the detailed mechanism; however, its association with decidual inflammation is unclear. A retrospective case control study was conducted in a single university. Subjects were cases who delivered by cesarean section between January 1, 2013 and June 30, 2020 and whose placentas were pathological assessed. CD was diagnosed by CD138 immunostaining of placental decidua tissue, and the perinatal prognosis and incidences of hypertensive disorder of pregnancy and preeclmpsia were examined according to the presence or absence of CD. A logistic regression analysis was performed to evaluate the association between preeclampsia and 11 explanatory variables (10 patient or perinatal background factors and CD). The study population included 76 patients (non-CD, n = 54; CD, n = 22). The rate of preeclampsia was significantly higher in the CD group ( P = 0.0006). Patients with CD gave birth at a significantly earlier gestational age ( P= 0.040) with a lower birth weight ( P = 0.001), and a higher rate of LFD ( P = 0.005). The Apgar scores at 1 and 5 min and umbilical artery pH were lower ( P = 0.0003, 0.021 and 0.002, respectively) in the CD group. The logistic regression analysis revealed that CD was positively associated with preeclampsia. A retrospective examination of the placenta found that patients with CD had a significantly higher incidence of preeclampsia and CD is considered to be a factor that is associated with poor perinatal outcomes.